Evaluation of Molluscicidal Activities of Aqueous and Ethanolic Extracts of Onion Bulb (Allium Sativum) Against Bulinus Wrighti - SARKINGOBIR, YUSUF (UNUSA Press, 2023)
Schistosomiasis is a disease of public health importance in the tropics and subtropics. However, the synthetic materials for prevention of the intermediate host of the disease are harmful, scarce, and toxic. Thus, an evaluation of molluscicidal activities of aqueous and ethanolic extracts of the bulb of Allium sativum against Bulinus wrighti were carried out. Snails were exposed to various concentrations of plant preparations in laboratory conditions in a plastic aquarium containing 3L of de-chlorinated water for 96h continuously. Mortality was recorded at every 24hours interval for 96hours. The study shows that, molluscicidal activities are time and dose dependent against snails. The ethanolic extract was more toxic than aqueous extract. Ethanolic extract of A. sativum was found highly toxic to B. wrighti (24hrs. LC50: 97.07mg/l; 96hrs: 21.70mg/l). Chemical profile of aqueous extracts of A. sativum showed the presence of some secondary metabolites. A. sativum extracts showed histopathological signs to hermaphrodite glands and the digestive tract of the treated snails. This study showed that, this plant can be used as molluscicides. This study recommends the use of ethanolic and aqueous extract of A. sativum for the control of B. wrighti.